Bridging soil mapping units and digital soil mapping through probability-driven machine learning: an uncertainty-aware framework for soil class prediction in Antarctica - Rafael G. Siqueira; Cássio M. Moquedace; Márcio R. Francelino; Carlos Ernesto G.R. Schaefer; Roberto F.M. Michel; Daniela Schmitz; Flávia R. Ferrari; Caroline Delpupo; Eduardo O. Senra; Heitor P. Palma; Daniel N. Krum; Fábio S. de Oliveira; et al. (CATENA, 2026)

Correction to: Impact of Regulation (EU) No. 536/2014 on clinical trial approval processes in two Italian oncology centers - Daniela Bencardino; Fabiana Marchetti; Cristina Mazzi; Marianna Ferrari; Francesca Garibaldi; Giulia Ferrera; Giulia Ponti; Chiara Altavilla; Laura Rossi; Matteo Verzè; Vanda Salutari; Vincenzina Mora; et al. (Journal of Pharmaceutical Innovation, 2026)

Impact of Regulation (EU) No. 536/2014 on clinical trial approval processes in two Italian oncology centers - Daniela Bencardino; Fabiana Marchetti; Cristina Mazzi; Marianna Ferrari; Francesca Garibaldi; Giulia Ferrera; Giulia Ponti; Chiara Altavilla; Laura Rossi; Matteo Verzè; Vanda Salutari; Vincenzina Mora; et al. (Journal of Pharmaceutical Innovation, 2026)

A sea of soap: toxicity of anionic surfactant to Clytia hemisphaerica (Hydrozoa) - Valentina Ferrari; Daniela Prevedelli; Elisa Bergami (Ecotoxicology, 2026)

Microbiological quality and allergen assessment of vegan-labelled foods sold in Turin - Sara Morello; Carla Ferraris; Clara Tramuta; Alessandra Provera; Samantha Lupi; Aitor Garcia-Vozmediano; Cristiana Maurella; Daniela Manila Bianchi (Journal of Consumer Protection and Food Safety, 2026)
The consumption of vegan-labelled foods has increased due to ethical, environmental, and health motivations, yet comprehensive evaluations of their microbiological safety and undeclared animal-derived allergens remain limited. This study analyzed 34 vegan products from Turin, Italy, using microbiological assays alongside biomolecular and immunoenzymatic techniques to detect crustacean and vertebrate DNA, as well as milk and egg proteins. Results showed no presence of Salmonella spp ., Listeria monocytogenes , milk, egg, or crustacean allergens; Enterobacteriaceae were detected within acceptable limits in 2 samples, and vertebrate DNA was found in one non-dairy cheese alternative. Overall, these findings indicate generally good hygienic quality and effective allergen management in the analysed products. These results provide baseline evidence to support future risk assessments and regulatory considerations in the plant-based food sector.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Cascade testing as the missing link in cancer prevention among Lynch syndrome families - Lea Godino; Giulia Erini; Giovanni Innella; Sara Miccoli; Simona Ferrari; Pamela Magini; Luca Caramanna; Martina Preite; Veronica Simoni; Daniela Turchetti (Familial Cancer, 2026)

Gene expression analysis and halting of ethylene receptors signaling pinpoint ethylene as a positive regulator of direct somatic embryogenesis in Coffea arabica - Natalia Gomes Vieira; Cesar Augusto Nascimento; Ilse Fernanda Ferrari; Mariana Silva Sartorello; Juliana Costa de Rezende; Daniela de Argollo Marques; Angelo Pedro Jacomino; Julieta Andrea Silva de Almeida; Jorge Maurício Costa Mondego (Planta, 2025)

The Italian Standardization of the Cerebellar Cognitive Affective/Schmahmann Syndrome Scale: Cognitive Profiling in a Healthy, Heterogeneous Population - Maria Devita; Adele Ravelli; Anna Panzeri; Anna Castaldo; Maria Arioli; Giusi Olivito; Angela Berardi; Alessandro Miscioscia; Chiara Ferrari; Libera Siciliano; Caterina Mariotti; Marina De Rui; et al. (The Cerebellum, 2025)

Environmental, climatic, socio-economic factors and non-pharmacological interventions: A comprehensive four-domain risk assessment of COVID-19 hospitalization and death in Northern Italy - Lucia Palandri; Cristiana Rizzi; Vittoria Vandelli; Tommaso Filippini; Alessandro Ghinoi; Giuliano Carrozzi; Gianfranco De Girolamo; Isabella Morlini; Paola Coratza; Enrico Giovannetti; Margherita Russo; Mauro Soldati; et al. (International Journal of Hygiene and Environmental Health, 2025)

Spatial Variation in Upper Limits of Coral Cover on the Great Barrier Reef - Mariana Álvarez‐Noriega; Juan C. Ortiz; Daniela M. Ceccarelli; Michael J. Emslie; Katharina E. Fabricius; Michelle J. Jonker; Marji Puotinen; Barbara J. Robson; Chris M. Roelfsema; Tane H. Sinclair‐Taylor; Renata Ferrari (Global Ecology and Biogeography, 2024)
Aim Identifying the maximum coral cover that a coral community can sustain (i.e., its ‘upper limit’) is important for predicting community dynamics and improving management strategies. Here, we quantify the relationship between estimated upper limits and key environmental factors on coral reefs: hard substrate availability, temperature and water clarity. Location Great Barrier Reef (GBR), Australia (over 1400 km). Time Period 1990 to 2022. Major Taxa Studied Scleractinian corals. Methods We used 32 years of data on coral cover around reef perimeters. Each reef was divided into four wave‐exposure habitats depending on prevailing wind conditions. For each site, we determined if hard coral cover had reached a plateau or upper limit. Next, we extracted existing estimates of hard substrate availability, modelled water temperature and Secchi depth. Then, we quantified the relationship between these environmental variables and the upper limits. Results We found varying upper limits across the GBR, with a median of 33% coral cover and only 17% of the estimated upper limits exceeded 50% coral cover. Upper limits increased towards the southern reefs. Our results show that upper limits increased with increasing hard substrate availability and decreased with temperature and, to a lesser extent, with water clarity. Main Conclusions The upper limits estimated in this study are much lower than what is commonly assumed when modelling ecological dynamics, most likely resulting in predicted recovery rates being inappropriately high. Although hard substrate ultimately restricted upper limits, there are mechanisms constraining the proportion of hard substrate that is covered by hard corals. The negative relationship between temperature and upper limits cannot be explained by changes in macroalgal abundance but may be related to changes in species composition. The quantitative relationships between the upper limits of coral cover and environmental variables will provide critical information to prioritise sites for management interventions.

Clinical and Histopathological Evolution of Acute Intraperitoneal Infection by Streptococcus agalactiae Serotypes Ib and III in Nile Tilapia - Natália Amoroso Ferrari; Leonardo Mantovani Favero; Cesar Toshio Facimoto; Alais Maria Dall Agnol; Marcos Letaif Gaeta; Thalita Evani Silva de Oliveira; Daniela Dib Gonçalves; Nelson Maurício Lopera-Barrero; Ulisses de Pádua Pereira; Giovana Wingeter Di Santis (Fishes, 2024)
Streptococcus agalactiae is a highly invasive bacterium that causes significant economic losses in tilapia aquaculture around the world. Furthermore, it is a pathogen for mammals, including humans, emphasizing its importance in One Health. The aim of this work was to evaluate the evolution of clinical and histopathological lesions caused by acute infection with two serotypes of S. agalactiae. For this, two strains isolated from natural outbreaks in Brazilian aquaculture farms (S13, serotype Ib; S73, serotype III) were used to challenge juvenile Nile tilapia (Oreochromis niloticus) intraperitoneally. Target organ samples were collected ten times, between 1 and 96 h post-infection, for microbiological and histopathological analyses. Anorexia was the first clinical sign and the first death occurred at 24 and 30 h in the fish infected with strains S13 and S73, respectively. Serotype Ib initially caused more pronounced lesions in the nervous system; however, serotype III lesions progressed more aggressively, reaching the same severity as those of serotype Ib. This trend was repeated in the mortality curve after 32 h. These results elucidated the important stages in the pathogenesis of S. agalactiae serotypes Ib and III in tilapia and suggest “tips and tricks” to improve the positive culture rate in the clinical diagnosis of infections in some tissues.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Combination of pH-shifting, ultrasound, and heat treatments to enhance solubility and emulsifying stability of rice protein isolate - Daniela E. Igartúa; M. Celeste Dichano; Sofia B. Ferrari; Gonzalo G. Palazolo; Dario M. Cabezas (Food Chemistry, 2024)

Morphological and metabolic changes in microglia exposed to cadmium: Cues on neurotoxic mechanisms - Federica Bovio; Elisa Perciballi; Pasquale Melchioretto; Daniela Ferrari; Matilde Forcella; Paola Fusi; Chiara Urani (Environmental Research, 2024)

Efficient utilization of monosaccharides from agri-food byproducts supports Chlorella vulgaris biomass production under mixotrophic conditions - Francesca Angelini; Erika Bellini; Angela Marchetti; Gaia Salvatori; Marianna Villano; Daniela Pontiggia; Simone Ferrari (Algal Research, 2024)

SARS-CoV-2 antibodies in inflammatory neurological conditions: a multicentre retrospective comparative study - Cecilia Zivelonghi; Alessandro Dinoto; Sarosh R. Irani; Andrew McKeon; Andrea Pilotto; Alessandro Padovani; Stefano Masciocchi; Eugenio Magni; Chiara R. Mancinelli; Ruggero Capra; Giorgia T. Maniscalco; Irene Volonghi; et al. (Immunologic Research, 2023)
It is well established that neurological and non-neurological autoimmune disorders can be triggered by viral infections. It remains unclear whether SARS-CoV-2 infection induces similar conditions and whether they show a distinctive phenotype. We retrospectively identified patients with acute inflammatory CNS conditions referred to our laboratory for antibody testing during the pandemic (March 1 to August 31, 2020). We screened SARS-COV-2 IgA/IgG in all sera by ELISA and confirmed the positivity with additional assays. Clinical and paraclinical data of SARS-COV-2-IgG seropositive patients were compared to those of seronegative cases matched for clinical phenotype, geographical zone, and timeframe. SARS-CoV-2-IgG positivity was detected in 16/339 (4%) sera, with paired CSF positivity in 3/16. 5 of these patients had atypical demyelinating disorders and 11 autoimmune encephalitis syndromes. 9/16 patients had a previous history of SARS-CoV-2 infection and 6 of them were symptomatic. In comparison with 32 consecutive seronegative controls, SARS-CoV-2-IgG-positive patients were older, frequently presented with encephalopathy, had lower rates of CSF pleocytosis and other neurological autoantibodies, and were less likely to receive immunotherapy. When SARS-CoV-2 seropositive versus seronegative cases with demyelinating disorders were compared no differences were seen. Whereas seropositive encephalitis patients less commonly showed increased CSF cells and protein, our data suggest that an antecedent symptomatic or asymptomatic SARS-CoV-2 infection can be detected in patients with autoimmune neurological conditions. These cases are rare, usually do not have specific neuroglial antibodies.

Effect of an organic acid blend in Nile tilapia growth performance, immunity, gut microbiota, and resistance to challenge against francisellosis - Vanessa Gomes da Silva; Leonardo Mantovani Favero; Raffaella Menegheti Mainardi; Natália Amoroso Ferrari; Roberta Torres Chideroli; Giovana Wingeter Di Santis; Felipe Pinheiro de Souza; Arthur Roberto da Costa; Daniela Dib Gonçalves; Waldo G. Nuez-Ortin; Maria Mercè Isern-Subich; Admilton Gonçalves de Oliveira-Junior; et al. (Research in Veterinary Science, 2023)

Specifications and validation of the ACMG/AMP criteria for clinical interpretation of sequence variants in collagen genes associated with joint hypermobility - Maria Pia Leone; Silvia Morlino; Grazia Nardella; Riccardo Pracella; Daniela Giachino; Luca Celli; Demetrio Baldo; Licia Turolla; Maria Piccione; Emanuela Salzano; Martina Busè; Patrizia Lastella; et al. (Human Genetics, 2023)

First evidence of population genetic structure of the deep-water blackmouth catshark Galeus melastomus Rafinesque, 1810 - Simone Di Crescenzo; Alice Ferrari; Claudio Barría; Rita Cannas; Alessia Cariani; Jim Drewery; Lourdes Fernández-Peralta; Daniela Giordano; Manuel Hidalgo; Vasiliki Kousteni; Ilaria Anna Maria Marino; Daniela Massi; et al. (Frontiers in Marine Science, 2022)
Among the main measures adopted to reduce anthropogenic impacts on elasmobranch communities, understanding the ecology of deep-sea sharks is of paramount importance, especially for potentially vulnerable species highly represented in the bycatch composition of commercial fisheries such as the blackmouth catshark Galeus melastomus . In the present work, we unravelled the first indication of population genetic structure of G. melastomus by using a novel and effective panel of nuclear, and polymorphic DNA markers and compared our results with previous findings supporting high genetic connectivity at large spatial scales. Given the lack of species-specific nuclear markers, a total of 129 microsatellite loci (Simple Sequence Repeats, SSRs) were cross-amplified on blackmouth catshark specimens collected in eight geographically distant areas in the Mediterranean Sea and North-eastern Atlantic Ocean. A total of 13 SSRs were finally selected for genotyping, based on which the species exhibited signs of weak, but tangible genetic structure. The clearcut evidence of genetic differentiation of G. melastomus from Scottish waters from the rest of the population samples was defined, indicating that the species is genetically structured in the Mediterranean Sea and adjacent North-eastern Atlantic. Both individual and frequency-based analyses identified a genetic unit formed by the individuals collected in the Tyrrhenian Sea and the Strait of Sicily, distinguished from the rest of the Mediterranean and Portuguese samples. In addition, Bayesian analyses resolved a certain degree of separation of the easternmost Aegean sample and the admixed nature of the other Mediterranean and the Portuguese samples. Here, our results supported the hypothesis that the interaction between the ecology and biology of the species and abiotic drivers such as water circulations, temperature and bathymetry may affect the dispersion of G. melastomus , adding new information to the current knowledge of the connectivity of this deep-water species and providing powerful tools for estimating its response to anthropogenic impacts.

Peripheral neuropathies during the COVID-19 pandemic: is there a relation? - Milena Trentinaglia; Giuseppe Lippi; Gian Luca Salvagno; Marianna G. Rispoli; Maria Vittoria De Angelis; Francesca Castellani; Daniela Alberti; Giorgia T. Maniscalco; Francesca Rossi; Mara Turri; Patrizia Rossi; Elisabetta Del Zotto; et al. (Immunologic Research, 2022)

Immunophenotypical characterization of paraneoplastic neurological syndrome patients: a multicentric study - Lorenzo Lorusso; Vincenza Precone; Ian K Hart; Bruno Giometto; Raffaele Pezzani; Gaelle K Ngonga; Stefano Paolacci; Daniela Ferrari; Giovanni Ricevuti; Ernie Marshall; Matteo Bertelli (Journal of Biosciences, 2021)

Neurological symptoms and axonal damage in COVID-19 survivors: are there sequelae? - Silvia Bozzetti; Sergio Ferrari; Serena Zanzoni; Daniela Alberti; Michele Braggio; Sara Carta; Francesco Piraino; Daniele Gabbiani; Domenico Girelli; Riccardo Nocini; Salvatore Monaco; Ernesto Crisafulli; et al. (Immunologic Research, 2021)
The persistence of neurological symptoms after SARS-CoV-2 infection, as well as the presence of late axonal damage, is still unknown. We performed extensive systemic and neurological follow-up evaluations in 107 out of 193 consecutive patients admitted to the COVID-19 medical unit, University Hospital of Verona, Italy between March and June 2020. We analysed serum neurofilament light chain (NfL) levels in all cases including a subgroup ( n = 29) of patients with available onset samples. Comparisons between clinical and biomarker data were then performed. Neurological symptoms were still present in a significant number ( n = 49) of patients over the follow-up. The most common reported symptoms were hyposmia ( n = 11), fatigue ( n = 28), myalgia ( n = 14), and impaired memory ( n = 11) and were more common in cases with severe acute COVID-19. Follow-up serum NfL values (15.2 pg/mL, range 2.4–62.4) were within normal range in all except 5 patients and did not differentiate patients with vs without persistent neurological symptoms. In patients with available onset and follow-up samples, a significant ( p < 0.001) decrease of NfL levels was observed and was more evident in patients with a severe acute disease. Despite the common persistence of neurological symptoms, COVID-19 survivors do not show active axonal damage, which seems a peculiar feature of acute SARS-CoV-2 infection.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Combination of Pretreatment with White Rot Fungi and Modification of Primary and Secondary Cell Walls Improves Saccharification - Charis Cook; Fedra Francocci; Felice Cervone; Daniela Bellincampi; Paul G Bolwell; Simone Ferrari; Alessandra Devoto (BioEnergy Research, 2015)

TNFα-induced endothelial activation is counteracted by polyphenol extract from UV-stressed cyanobacterium Arthrospira platensis - Pier Francesco Ferrari; Daniela Palmieri; Alessandro A. Casazza; Bahar Aliakbarian; Patrizia Perego; Domenico Palombo (Medicinal Chemistry Research, 2015)

Polyomavirus JC reactivation and noncoding control region sequence analysis in pediatric Crohn's disease patients treated with infliximab - Anna Bellizzi; Elena Anzivino; Federica Ferrari; Giovanni Di Nardo; Maria Teresa Colosimo; Daniela Fioriti; Monica Mischitelli; Fernanda Chiarini; Salvatore Cucchiara; Valeria Pietropaolo (Journal of NeuroVirology, 2011)

The surface roughness of lactose particles can be modulated by wet-smoothing using a high-shear mixer - Franca Ferrari; Daniela Cocconi; Ruggero Bettini; Ferdinando Giordano; Patrizia Santi; Michael Tobyn; Robert Price; Paul Young; Carla Caramella; Paolo Colombo (AAPS PharmSciTech, 2004)